2011
DOI: 10.1371/journal.pone.0025596
|View full text |Cite
|
Sign up to set email alerts
|

A Reference Proteomic Database of Lactobacillus plantarum CMCC-P0002

Abstract: Lactobacillus plantarum is a widespread probiotic bacteria found in many fermented food products. In this study, the whole-cell proteins and secretory proteins of L. plantarum were separated by two-dimensional electrophoresis method. A total of 434 proteins were identified by tandem mass spectrometry, including a plasmid-encoded hypothetical protein pLP9000_05. The information of first 20 highest abundance proteins was listed for the further genetic manipulation of L. plantarum, such as construction of high-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…On the contrary, PDH subunit D was expressed also in the wild type strain, regardless of growth condition and, in the mutant strain, it was expressed at lower level under aeration. It is worth to notice that the present study highlighted the expression of PDH subunits in L. plantarum WCFS1 at proteomic level, as it has been very recently observed also in L. plantarum CMCC-P0002 [43].…”
Section: Discussionsupporting
confidence: 80%
“…On the contrary, PDH subunit D was expressed also in the wild type strain, regardless of growth condition and, in the mutant strain, it was expressed at lower level under aeration. It is worth to notice that the present study highlighted the expression of PDH subunits in L. plantarum WCFS1 at proteomic level, as it has been very recently observed also in L. plantarum CMCC-P0002 [43].…”
Section: Discussionsupporting
confidence: 80%
“…Moonlighting activities may be hypothesized for many of the above proteins, as their abundance is predominantly affected at the extra‐cytoplasmic level. Some of these proteins have also been identified in the exoproteome of other lactobacilli . In accordance with the cytoplasmic level of some glycolytic enzymes (e.g., PKI and PGM), the lowest level of catabolite control protein A (CcpA) was found in the biofilm culture; however, a positive role for the master regulator catabolite control protein A in biofilm development was previously reported .…”
Section: Discussionmentioning
confidence: 61%
“…Elongation factors are necessary for the repair of the damaged structural protein, by incorporating amino acids into the growing or impaired polypeptide chain ( Nilsson and Nissen, 2005 ). On the other hand, EF-Tu, and several cytoplasmic proteins (e.g., DnaK, GroES, GroEL, GAPDH), are considered to be multi-functional (called “moonlighting’ proteins), with additional functions usually acquired after modification by glycosylation or phosphorylation ( Le Maréchal et al ., 2015 ; Zhu et al ., 2011 ). In previous studies, EF-Tu was found to play a major role in bacterial colonization of the porcine gut, through its intrinsic property and high affinity for sulfurylated mucus layers ( Danielsen et al ., 2007 ; Nishiyama et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%